Airborne‐radar and ice‐core observations of annual snow accumulation over Thwaites Glacier, West Antarctica confirm the spatiotemporal variability of global and regional atmospheric models. Issue 14 (26th July 2013) - Medley, B.; Joughin, I.; Das, S. B.; Steig, E. J.; Conway, H.; Gogineni, S.; Criscitiello, A. S.; McConnell, J. R.; Smith, B. E.; van den, M. R.; Lenaerts, J. T. M.; Bromwich, D. H.; et al.
Abstract [1] We use an airborne‐radar method, verified with ice‐core accumulation records, to determine the spatiotemporal variations of snow accumulation over Thwaites Glacier, West Antarctica between 1980 and 2009. We also present a regional evaluation of modeled accumulation in Antarctica. Comparisons between radar‐derived measurements and model outputs show that three global models capture the interannual variability well (r > 0.9), but a high‐resolution regional model (RACMO2) has better absolute accuracy and captures the observed spatial variability (r = 0.86). Neither the measured nor modeled accumulation records over Thwaites Glacier show any trend since 1980. Although an increase in accumulation may potentially accompany the observed warming in the region, the projected trend is too small to detect over the 30 year record.